Dynamics of fecal microbiota in hospitalized elderly fed probiotic LKM512 yogurt - Matsumoto, Mitsuharu; Sakamoto, Mitsuo; Benno, Yoshimi (Microbiology and immunology, 2009)
ABSTRACT The comprehensive dynamics of intestinal microbiota including uncultured bacteria in response to probiotic consumption have not been well studied. The aims of this study were twofold: firstly to analyze the impact on intestinal microbiota of yogurt fermented by Bifidobacterium animalis subsp. lactis LKM512, Lactobacillus delbrueckii subsp. bulgaricus LKM1759, and Streptococcus thermophilus LKM1742 (LKM512 yogurt) and placebo fermented by these lactic acid bacterial strains without LKM512; and secondly to investigate the changes in intestinal microbiota that influence the concentration of PA, one of the beneficial metabolites produced by bacteria in the intestine. The LKM512 yogurt/placebo trial was performed in six hospitalized elderly patients (three men and three women with an average age of 80.3 years) and lasted seven weeks with the following schedule: pre‐consumption for one week, LKM512 yogurt consumption for two weeks, washout period for two weeks, and placebo consumption for two weeks. The amount of ingested LKM512 yogurt or placebo was 100 g/day/individual. Fecal samples were analyzed using T‐RFLP and real‐time PCR. The T‐RFLP patterns in five of the six volunteers were changed in a similar fashion by LKM512 yogurt consumption, although these patterns were individually changed following consumption of placebo. It was confirmed that B. animalis subsp. lactis was increased dramatically and Lactobacillus spp. tended to be decreased by LKM512 yogurt consumption. Some indigenous uncultured bacteria were increased and some decreased by LKM512 yogurt/placebo consumption. The similar changes in the intestinal microbiota of the elderly caused by consumption of the LKM512 yogurt were found to be influenced by the LKM512 strain itself, and not by the lactic acid bacteria in the yogurt. Moreover, this study suggests that the increase in intestinal PA concentrations caused by LKM512 yogurt consumption is probably dependent on the LKM512 strain colonizing the intestine.